Cell-based approaches for tendon regeneration - Gonçalves, A. I. (2015)
Cell based therapies have been proposed as potential alternative solutions towards efficient regenerative strategies for damaged tendon tissues. These approaches traditionally envision the delivery of cells, mostly stem cells or tendon cells, often combined with carriers and growth factors to provide the behavioral instructions similar to the ones found in native tissues. The purpose of cell based therapies is to apply living cells to guide and promote enhanced tissue repair and functional regeneration of an injured or diseased tissue. This chapter will focus on the potential of several cell sources, including stem cells from different origins, in tendon regeneration, illustrated by their therapeutic role in animal models of tendinopathies. Furthermore, it will be also addressed experimental cellular therapies currently ongoing in clinical trials that hold the promise for innovative clinical outcomes in tendon regeneration.